Use of an isothermal microcalorimetry assay to characterize microbial oxalotrophic activity - Bravo, Daniel; Braissant, Olivier; Solokhina, Anna; Clerc, Martin; Daniels, Alma U.; Verrecchia, Eric; Junier, Pilar (My University, 2011)
Isothermal microcalorimetry (IMC) has been used in the past to monitor metabolic activities in living systems. A few studies have used it on ecological research. In this study, IMC was used to monitor oxalotrophic activity, a widespread bacterial metabolism found in the environment, and particularly in soils. Six model strains were inoculated in solid angle media with K-oxalate as the sole carbon source. Cupriavidus oxalaticus, Cupriavidus necator, and Streptomyces violaceoruber presented the highest activity (91, 40, and 55 μW, respectively) and a maximum growth rate (μmax h−1) of 0.264, 0.185, and 0.199, respectively, among the strains tested. These three strains were selected to test the incidence of different oxalate sources (Ca, Cu, and Fe-oxalate salts) in the metabolic activity. The highest activity was obtained in Ca-oxalate for C. oxalaticus. Similar experiments were carried out with a model soil to test whether this approach can be used to measure oxalotrophic activity in field samples. Although measuring oxalotrophic activity in a soil was challenging, there was a clear effect of the amendment with oxalate on the metabolic activity measured in soil. The correlation between heat flow and growth suggests that IMC analysis is a powerful method to monitor bacterial oxalotrophic activity.
Keywords: isothermal microcalorimetry (IMC); oxalotrophic activity; oxalotrophic bacteria